Security Drones: Is the Singapore Public Ready? - Muhammad Faizal Bin Abdul Rahman (2016)
The Singapore Home Team is leveraging technology, such as drones for operational efficacy, in support of the SG Secure movement. A powerful tool, the use of drones for homeland security must be accompanied by clear guidelines and with public trust.